INTERNAL FRAUD AT SYARIAH BANKING IN INDONESIA IS A CERTAINTY - Hamdani Hamdani (The Accounting Journal of Binaniaga, 2016)
This research has been describing an internal fraud happened at Syariah Banking in Indonesia. The development of Syariah banking should have to be in compliance with a good internal controlling system and management, otherwise, the internal fraud would happen either internally or externally. The bank with syariah principles should have to be applied accordingly in order to avoid any internal fraud happened in it which is tauhid, syariah and moral values. Nevertheless, such a value application is not quite easy to be implemented refers to Nabi Muhammad SAW has been shown the implementation of shidiq, fatonah, amanah and tabligh (ShiFat).Keyword : Internal fraud